ANALISIS PENGUKURAN KINERJA DENGAN SISTEM BALANCED SCORECARD PADA RUMAH SAKIT YOS SUDARSO PADANG (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2012)
This study describes the use of the Balanced Scorecard as a measure of hospital performance. The formulation of the problem is how the performance of Yos Sudarso Hospital when assessed by a financial perspective. The purpose of this study was to determine the performance of Yos Sudarso Hospital when assessed by a financial perspective. This research was conducted at the Yos Sudarso Hospital Padang in November 2003 to January 2004. Types of data collected is primary data in the form of interviews with the hospitals and secondary data from a general overview of the company, the income statement of 2000 to 2002, the balance sheet of 2000 to 2002 and other documents that support. Techniques of data collection are interview and observation techniques. While the data analysis techniques used in the financial perspective is ROI, ROA, Current Ratio, Quick Ratio, Receivables Turnover, Average Collection Period, Asset Turnover. The results of this study are as follows: Hospital Performance ODOT Padang is the first ROI in 2002 increased 1% respectively from 2000 and 2001, ROA from 2001 to 2002 did not increase, current ratio in 2002 decreased their respectively (5.60%) and (16.60%), Quick Ratio at the end of 2002 compared with the end of 2001 and 2000 also decreased respectively (5.90%) and (17.90%), Average collection In 2002 the time period it takes to collect receivables is 10 days results decreased compared to 2001 and 2000 respectively was 3 days and 4 days, Asset turnover in 2002 was 1.67 times also decreased each is equal to (0.16) times and (0.56) times.